TEACHERS’ CREATIVITY IN DESIGNING TEACHING AIDS TO IMPROVE STUDENTS’ LEARNING OUTCOMES AT GRADE IV SD INPRES TOBU - Imanuel Y Faot (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Students tend to experience difficulties in learning mathematics, one of which is seen from the very low score of students' mathematics report cards. Meanwhile, success means to achieve learning objectives. In fact, there is a situation in which students still find it difficult to understand the material being taught. Mathematics is perceived as a boring, uninteresting, and difficult subject to understand, and learning is always teacher centered. This study aimed to determine the increase of students’ learning outcomes and the implementation of learning using teaching aids. This research was conducted at SD Inpres Tobu and the research subjects were 20 grade IV students. The data were collected through tests and observation sheets. Based on the results of the analysis, it could be concluded that there was an increase in students’ learning outcomes after utilizing teaching aids in Mathematics in the material of geometry and cubes at grade IV SD Inpres Tobu for the academic year 2019/2020.